Tópicos de física moderna e contemporânea no ensino médio : interfaces de uma proposta didática para mecânica quântica - Biazus, Marivane de Oliveira (2015)
The present study is an investigation about the inclusion of Modern and Contemporary Physics (MCP) in high school. Specialized literature has indicated that, although it is a relevant subject for students in this school level, there is little didactic material at the point of use for teachers, especially if considering the need and relevance of relating the content to daily life situations of the students. The research was included in the line of methodological and theoretical foundations for teaching Sciences and Mathematics, and sought to discuss the implications for students access to MCP, more specifically Quantum Mechanics, when using diverse didactic materials related to their daily life. Thus, an objective outlined in the study was to develop a didactic sequence for approaching MCP topics in high school, hence resorting to different didactic tools and assessing their relevance. As for theoretical support, didactic transposition by Yves Chevallard s perspective was used, aiming to analyze the path made by a piece of content, since its production in the scientific community up to its introduction to the classroom. Moreover, the study sought support in Lev Semenovich Vygostsky s social interactionist theory to study the didactic sequence and guide its application in the classroom. Such didactic sequence was structured in twenty meetings that discussed quantum mechanics through videos, documentaries, simulators, experimental activities, among other different didactic tools. The didactic proposal was applied in a group of twenty senior high school students of a public school, in the city of Passo Fundo, RS, Brazil. In order to become an aid for other teachers, the different didactic tools used in the sequence, as well as the material written as a booklet and other resources compiled and adapted from the literature available, were gathered in a website, which is the educational product of this dissertation and is available in the Postgraduate Program in Education for Sciences and Mathematics page for free access. Lastly, data collection, which aimed to answer the initial question, was performed with two research instruments: pre- and post-test questionnaire, and a logbook. Both instruments allowed inferring that the use of diverse tools related to daily life situations of the students, as well as the didactic choice of structuring the activities within a perspective that strives for dialogue and interaction, helps students to be more motivated, interested, and close to MCP.